The Influence of the Coaching System, Infrastructure and Training Education on Teacher Performance Competence - Daman Rasman Syarif Hidayat (Institute of Computer Science (IOCS), 2021)
Numerous factors can be used as indicators of a school's excellence and quality. These factors include the quality of teaching and learning processes in schools, the completeness of facilities and infrastructure, the professionalism of human resources, academic achievement, and the management quality of schools. This study utilizes qualitative case studies. This study collected data through interviews, literary analysis, field observations, and documentation. The investigation took place concurrently with the data collection on the ground in this research. The researcher reduces data obtained by analyzing it, sorting it, focusing on research, and drawing conclusions in all directions. The validity of the data in this study is determined by using triangulation techniques (solutions and methods/techniques), observations, and member controls. As demonstrated in this study, the coaching system, infrastructure, education, and training all directly affect teacher competence. Meanwhile, the coaching system and infrastructure have a direct impact on teacher performance. It has not been established that education and training directly impact the performance of teachers at Pluit Raya Jakarta Junior High School in elementary school. The coaching system, infrastructure, and education do not directly affect teachers' performance at Pluit Raya Elementary School Jakarta. Still, competence does not affect the performance of teachers at Pluit Raya Elementary School Jakarta directly.